The Last Farewell Embrace: Spirituality, Near-Death Experiences, and Other Extraordinary Events among Nurses by Alejandro Parra - Tucker, Jim (Journal of Scientific Exploration, 2020)
Alejandro Parra, a psychologist who teaches at the Universidad Abierta Interamericana, is the author of several books, including one on the history of parapsychology in Argentina. In his latest, he writes about his interviews with dozens of nurses and professional caregivers regarding exceptional experiences that they either witnessed in patients, often at the end of life, or had themselves. As an example, a psychiatric nurse in Buenos Aires told about a patient who woke up at four o’clock one morning, shouting “My house is on fire, my house is on fire!” The distraught woman tried to leave the hospital and eventually had to be sedated with medication. Two days later, relatives arrived with objects that had been rescued from a fire at her house, which had occurred at four in the morning.